Carbapenem-Resistant Enterobacteriaceae Bloodstream Infection Treated Successfully With High-Dose Meropenem in a Preterm Neonate - Wu, Yue-E; Xu, Hai-Yan; Shi, Hai-Yan; van den Anker, John; Chen, Xiao-Yu; Zhao, Wei (Frontiers in Pharmacology, 2020)
Carbapenem-resistant enterobacteriaceae (CRE) bloodstream infections have been rapidly spreading worldwide with a high mortality and poses a challenge to therapeutic decision-making, especially in premature neonates, because insufficient empirical antimicrobial therapy is independently associated with high mortality. This case reported that a premature infant with CRE bloodstream infection was treated successfully by high-dose meropenem treatment with model-based therapeutic drug monitoring (TDM). In clinical settings, treatment target attainment of meropenem can be improved by increasing the frequency of administration, prolonging the infusion time, and using a high dose. This case report shows a successful regimen for CRE infection in a premature neonate and emphasizes the utility of model-based TDM of high-dose meropenem treatment. The adequate antimicrobial benefit provided by innovative techniques could ensure the efficacy and safety of high-dose meropenem therapy for CRE infection.